Julian Anderson: Dialogues on Listening, Composing and Culture - Anderson, Julian -1967; Dingle, Christopher (Woodbridge Boydell, 2020)
Julian Anderson is renowned internationally as one of the leading composers of his generation. This substantial book of conversations with the scholar and critic Christopher Dingle captures Anderson's thoughts and memories in-depth for the first time, not only providing essential biographical information and background material, but also capturing the workings of a remarkable mind. It is rare to find a composer prepared to speak as extensively, on as broad a range of topics or as honestly as Anderson. Unlike some composers, his extraordinarily diverse musical interests range far beyond the aesthetic of his own compositions. Crucially, the conversations frequently range beyond Anderson's own works, or even beyond the sphere of music, exploring issues of broader cultural interest. Providing for insights into the practicalities and psychology of composing, of particular value are the glimpses of Anderson's thoughts on works in progress, including the period from finishing the score for his ENO opera Thebans to its first production, as well as his violin concerto and his Berlin Philharmonic commission Incantesimi. While these conversations reflect the fact that Anderson is first and foremost a composer, his extensive cultural hinterland is also apparent. Revealing much about the workings of the musical world, these conversations will not only be essential reading for composers and composition students, but also contemporary music lovers more generally.
Includes bibliographical references, discography and index.
Keywords: Composer; Composing; Music philosophy and esthetics; United Kingdom